Valuing quality of vegetation in recharge area of Seruk Spring, Pesanggrahan Valley, Batu City, East Java - TITUT YULISTYARINI; SITI SOFIAH (Biodiversitas Journal of Biological Diversity, 2011)
Yulistyarini T, Sofiah S (2011) Valuing quality of vegetation in recharge area of Seruk Spring, Pesanggrahan Valley, Batu City, East Java. Biodiversitas 12: 229-234. A Seruk spring is one of the springs in Batu city which has water debit less than 1 liter per second. Land use changes of Seruk spring recharge area was occurred in 2001. Recharge area of Seruk Spring consists of anthropogenic forest, eucalypts plantation, bamboo forest, pines plantation, horticulture and housing. The aim of this research was to valuing the quality of vegetation which supported ground water recharge in Seruk spring. Quality of vegetation was determined by vegetation structure, diversity, the thickness of litter and C-stock of each land use systems. Forests, eucalypts plantation and bamboo forests had almost same quality of vegetation.